The Characteristics and Knowledge of Family of Patients with CKD about AV- Shunt At Dr. Zainoel Abidin General Hospital - Rivai, Mohammad Arif; Junaidi, Fachrul; Khalilullah, Saif Alvin; Muzakkir, Yumna (Surgical Residency Program Syiah Kuala University, 2023)
Introduction: Identifying the CKD progression of the patient should be presented with a range of choices for renal replacement treatment. Therefore, establishing vascular access for hemodialysis is significantly correlated with the survival rate of patients as well as knowledge related to access. Thus, in this study, we aim to report the characteristics and knowledge of the family of patients with CKD about AV-shunt at Dr. Zainoel Abidin General Hospital. Method: This research is descriptive research with a retrospective approach. This study evaluated the